Perancangan dan Implementasi Sistem Informasi Perpustakaan Gelatik Aksara Berbasis Web - Hidayat, Irfan; Hidayat, Hidayat (Universitas Sulawesi Barat, 2024)
The low literacy culture in Indonesia is a complex problem. This low literacy hinders the development of individuals and society, and has an impact on the low quality of human resources. One of the main problems is the lack of access to quality reading materials, especially in areas that cannot reach libraries. This study aims to design and implement a website-based information system in a small library Gelatik Aksara website to increase efficiency and effectiveness in managing the library. The software development method used is the waterfall model. This method includes the stages of needs analysis, system design, implementation, testing, and maintenance. The designed web-based system is built using PHP and MySQL programming. The results of system testing carried out using the black box method show that the system built can run well. Testing of users through questionnaires shows that the system built can help make it easier for users to search for and borrow and return books. In addition, the management process also becomes easier and more effective. This study contributes to the development of a small library management system that can be implemented for people in areas that have difficulty accessing books but have good literacy interests.